Analgesic treatment in non-cancer chronic pain - Duarte, Nuno (2023)
This book has been developed to support the curricular units of the Bachelor and Master study cycles of the School of Health of the Polytechnic Institute of Porto, which address the analgesic pharmacotherapy of chronic non-cancer pain. The aim of this book is to provide an overview of the pharmacological agents used in the treatment of chronic pain, focusing on the mechanism of action, indications, and adverse effects. This book analyzed the information available in articles on conventional drugs used in the treatment of chronic pain, including randomized controlled trials, open trials, and systematic reviews with or without meta-analysis. Newer drugs with potential off-label use were also included. Information on outcomes related to pain relief, safety/tolerability profile, or both was also included.